Observation of a nonlocal conductivity in the mixed state of YBa2Cu3O7-d: Experimental evidence for a vortex line liquid - Nieva, Gladys; Safar, H.; Gammel, P.L.; Huse, D.A.; Majumdar, S.N.; Schneemeyer, L.F.; Bishop, D.J.; Lopez, D.; Nieva, G.L.; de la Cruz, F. (American Physical Society, 1994)
Fil: Lopez, D. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina